ARAL CULTURE SUMMIT: A NEW STAGE OF ENVIRONMENTAL AND CULTURAL COOPERATION (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the role and significance of the Aral Culture Summit, held in the Republic of Karakalpakstan in 2024, as a pivotal initiative in addressing the ecological catastrophe of the Aral Sea region. Emphasizing Uzbekistan’s multifaceted approach to environmental recovery, cultural revitalization, and international cooperation, the article analyzes the Summit’s key contributions and long-term implications for regional sustainability.